Nephrologists’ Views on a Workflow for Returning Genetic Results to Research Participants - Robyn Weiss; Hila Milo Rasouly; Maddalena Marasa; Hilda Fernandez; Fangming Lin; Maya Sabatello (Kidney International Reports)
Introduction: Returning research-based genetic results (gRoR) to participants in nephrology research can improve care; however, the practice raises implementational questions and no established guidelines for this process currently exist. Nephrologists' views on this issue can inform the process but are understudied. Methods: We developed a conceptual workflow for gRoR from literature and experience, covering aspects such as which results to return, how, and by whom. We surveyed US nephrologists to gauge their views on the workflow and anticipated barriers and collected participants' demographics, including professional backgrounds. Results: A total of 201 adult and pediatric nephrologists completed the survey. Most of them agreed that all diagnostic kidney-related results (93%), secondary findings (80%), and kidney-related risk variants (83%) should be returned. No significant differences were found between adult and pediatric nephrologists’ responses, except that 48% of adult nephrologists versus 26% of pediatric nephrologists supported returning polygenic risk scores (PRS) (P < 0.01). Seventy-nine percent wanted to know about research results before clinical confirmation. Most of them (63%) believed a genetic counselor should return clinically confirmed results. Key barriers included the cost of clinical validation (77%) and the unavailability of genetic counseling services (63%). Facilitators included educational resources on genetic kidney diseases (91%), a referral list of experts (89%), and clear clinical care guidelines (89%). We discuss findings’ implications and provide “points to consider.” Conclusion: There is significant interest in gRoR among nephrologists; however, logistical and economic concerns need addressing. Identified facilitators can help large nephrology studies planning to return genetic results to participants.